The Influence of Human Resources, Information Technology, and Internal Control Systems on Budget Preparation with External Factors as Moderating Variables - Mega Arthika Dewi; Unggul Purwohedi; IGKA Ulupu (Journal of World Science, 2024)
This research aims to determine the effect of Human Resources, Information Technology, and Internal Control System on budget preparation by considering external factors as moderating variables. The focus of this research is the planning staff at Lemdiklat Polri and its ranks, which include Lemdiklat Polri, 34 SPN, and 15 Pusdik. The method used in this study is quantitative, using the SmartPLS 4.0 program. Data were collected through a survey of 50 respondents of planning staff in Lemdiklat Polri and its ranks. The results showed that Human Resources had no significant effect on budget preparation. In contrast, Information Technology and Internal Control System have a significant influence on budgeting. However, external factors do not moderate the influence of the Internal Control System on budget preparation. The implications of this study include providing theoretical contributions that show that the effectiveness of Information Technology and the strength of the Internal Control System are significant in the budgeting process. Practically, the results of this study provide recommendations to Lemdiklat Polri to further optimize the use of information technology and strengthen the internal control system to improve efficiency and accuracy in budget preparation.